Basic Principle and Contact Analysis of Internal Meshing Gear Drive with Curve Configuration - Dong Liang; Sheng Meng; Ming Li; Xiangyang Xu; Zeyin He (Jixie chuandong)
Based on gear transmission conjugate-curve theory research， taking the internal meshing gear transmission with curve element as the object， general meshing equation of spatial conjugate curves along the designated contact angle position is derived and general expressions of space conjugate curves under internal contact conditions are also obtained. According to space equidistant-enveloping method， conjugate surfaces which inherit the meshing characteristics of spatial conjugate curves are generated and three contact types including convex-to-convex， convex-to-plane and convex-to-concave forms are proposed if changing the relative motion position and equidistant radius. Taking the spatial cylindrical spiral curve as an example， combined with the theoretical analysis results and given design parameters， three-dimensional solid models of internal meshing gear pair with convex-to-concave contact are established. The pressure angle on the tooth surface contact point is defined and calculation method of sliding ratio for the mated tooth surfaces is also put forward in terms of space conjugate curves. Calculation and analysis of the contact locus of conjugated internal meshing tooth surfaces are conducted. Further studies on meshing characteristics， contact mechanics and manufacturing method of tooth profiles will be carried out.